Mobilidade pendular: Uma proposta teórico-metodológica - Rafael Henrique Moraes Pereira; Verónica Herrero (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– Recent studies point to commuting as a key element to understand regional dynamics and urban integration. This study propose three ideal types (Max Weber) of commuting flows based on its relations with social processes which impact urban structure by affecting residence and job locations in urban space. These processes (urban concentration, urban suburbanization and economic deconcentration) synthesize the elements which affect commuting patterns and commuters`socioeconomic characteristics. The article explores commuting data in metropolitan region of Campinas (Brazil) and in the urban agglomeration of Grande Buenos Aires (Argentina) in a way to point the importance of a framework able to identify its internal heterogeneities hidden by strictly descriptive analysis. The article also presents an attempt to operationalization of the typology for the metropolitan region of Campinas.
Keywords: R10; R23; R30; R40; 330